Energizing respites from work: a randomized controlled study on respite interventions - Steidle, Anna; Michel, Alexandra (European journal of work and organizational psychology, 2017)
Increasing and new work demands drain employees’ energy resources at work. This 4-week longitudinal field experiment investigated the energizing potential of a respite intervention conducted at the workplace (either a simulated savouring nature intervention or a progressive muscle relaxation intervention). First, growth modelling analyses confirmed a linear trend for the growth of vigour and decline in fatigue across the days of the intervention group, indicating a typical upward resource trajectory. No changes appeared in the control group. Mediation analyses indicated that repeatedly engaging in a daily respite intervention influenced more stable energy levels after the intervention period indirectly through the immediate changes in daily energy levels during the intervention period. Findings suggest that, in some cases, respite interventions may present a useful tool to replenish and build energy resources at work. Implications for using respite intervention in organizational research and practice are discussed.
Gesehen am 14.09.2018